An Innovative Approach in Developing Standard Professionals by Involving Software Engineering Students in Implementing and Improving International Standards - Laporte, Claude Y. (2015)
Today, the ability of organizations to compete, adapt, and survive depends increasingly on software. Some cellular phones, for example, contain over twenty million lines of code, and top of the line automobiles may have up to 100 million lines of code.1 Manufacturers depend increasingly on the components produced by their suppliers. A manufacturing chain of large mass-market products often has a pyramidal structure, as illustrated in Figure 1, adapted from Shintani.2 For example, a large mass product manufacturer integrated into one of its products a part with an unknown software error that was produced by one of its 6,000 lower-level producers. This defective part resulted in a loss of over $200 million by the mass product manufacturer. A vast majority of these low level suppliers are very small entities